MALT lymfom zaludku - kazuistika - Zálabská, Eva; Bareková, Lucie; Klobučar, Darko; Hanovcová, Irena (Klinicka mikrobiologie a infekcni lekarstvi, 2011)
Gastrointestinal tract is the most commonly (40 %) affected site of the extranodal forms of primary non-Hodgkin's lymphomas. Almost half of them are indolent lymphomas, mainly MALT lymphomas. The development of MALT lymphoma temporarily depends on antigen stimulation of Helicobacter pylori. More than 90 % of MALT lymphoma patients are positive for Helicobacter pylori antibodies, but the positivity of biopsy is present in only 60 % of them. Antibiotic therapy in Helicobacter pylori infection may lead to complete regression of the localized primary gastric lymphoma of the MALT type without any anti-tumour therapy. The aim of the case report is to present the disease in the context of possible antibiotic therapy of the tumour.
Keywords: lymfom z B-buněk marginální zóny; infekce vyvolané Helicobacter pylori; Helicobacter pylori; nádory žaludku; dospělí; mužské pohlaví; Adult; lidé; Male; Helicobacter Infections; Lymphoma, B-Cell, Marginal Zone; Humans; Stomach Neoplasms